Effect of Phosphatase and Tensin Homologue on Chromosome 10 on Angiotensin II-Mediated Proliferation, Collagen Synthesis, and Akt/P27 Signaling in Neonatal Rat Cardiac Fibroblasts. (25th September 2016) - Nie, Ling; Zhao, Jing-Hong; Wang, Jiang; Song, Rong; Zhu, Shan-Jun
Abstract : Cardiac fibroblasts (CFs) play a key role in cardiac fibrosis by regulating the balance between extracellular matrix synthesis and breakdown. Although phosphatase and tensin homologue on chromosome 10 (PTEN) has been found to play an important role in cardiovascular disease, it is not clear whether PTEN is involved in functional regulation of CFs. In the present study, PTEN was overexpressed in neonatal rat CFs via recombinant adenovirus-mediated gene transfer. The effects of PTEN overexpression on cell-cycle progression and angiotensin II- (Ang II-) mediated regulation of collagen metabolism, synthesis of matrix metalloproteinases, and Akt/P27 signaling were investigated. Compared with uninfected cells and cells infected with green fluorescent protein-expressing adenovirus (Ad-GFP), cells infected with PTEN-expressing adenovirus (Ad-PTEN) significantly increased PTEN protein and mRNA levels in CFs (P < 0.05 ). The proportion of CFs in the G1/S cell-cycle phase was significantly higher for PTEN-overexpressing cells. In addition, Ad-PTEN decreased mRNA expression and the protein synthesis rate of collagen types I and III and antagonized Ang II-induced collagen synthesis. Overexpression of PTEN also decreased Ang II-induced matrix metalloproteinase-2 (MMP-2) and tissue inhibitor of metalloproteinase-1 (TIMP-1) production as well as gelatinase activity. Moreover, Ad-PTEN decreased Akt expression and increased P27 expression independent of Ang II stimulation. These results suggest that PTEN could regulate its functional effects in neonatal rat CFs partially via the Akt/P27 signaling pathway.